CRITICAL REALISM OF AL-KINDÎ ON ARISTOTLE'S THEORY OF CREATION - Nur Hadi Ihsan; Elit Ave Hidayatullah; Sofyan Atstsauri (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
This study aims to expose al-Kindi's theory of creation and his repudiation of Aristotle's equivalent theory. The theory of creation was one of the philosophical problems that originated in the Greco-Aristotle philosophy. In this tradition, "creation" refers to making or changing something from something else. In other words, this universe was created from pre-existing matters, materials, and substratum. This viewpoint ran counter to Muslim beliefs, including al-Kindi. For al-Kindi, creation entails creating something from nothing. This universe did not exist before. God's qudrah determined its existence, and His iradah created it from nothing. To defend his position, al-Kindi used both philosophical and theological arguments. Like mutakallimun, al-Kindi's theological argument is built on the Qur'anic term "kun,” while his philosophical argument is based on the argument of limitations. This study is literature-based research using a descriptive critical analytical method. The data for this study were obtained from books, articles, and other written documents. The collected data is examined utilizing the critical analytical method. This research concludes that al-Kindi explained the concept of creation quite clearly, and succeeded in making an appropriate and directed critical response to Aristotle's theory of creation. Likewise, al-Kindi's idea of creation demonstrates his close position with theologians and separates himself from the Peripatetic philosophers after him, even though al-Kindi is famous as a Muslim philosopher.